The status of Fairy Pitta in Indonesia with new records from Java and Riau Islands - Syahras Fahin Aminuddin; Alexander Kurniawan Sariyanto Putera; Naila Zackeisha; Taufan Nurzaman Sulaeman; Arfah Nasution (KUKILA, 2020)
The Fairy Pitta Pitta nympha is an uncommon migrant known to visit Borneo during the non-breeding season. However, within Indonesia there are no published records of this species outside Kalimantan (Indonesian Borneo). We encountered single immature Fairy Pittas at Anambas island (Riau islands, Sumatra) in October 2019, and in Bogor and Jakarta (Java) in November 2019, suggesting an influx of young birds migrating beyond their normal wintering grounds.